A Most General and Facile Recipe for the Calculation of Heteroepitaxial Strain. Issue 12 (12th August 2020) - Grundmann, Marius
Abstract : A general approach to the calculation of heteroepitaxial strain for arbitrary crystal symmetry (including triclinic) and arbitrary interface plane is presented. The formulas are easily implemented into an algebraic math program. Particular results are derived for rhombohedral heterostructures. Abstract : An easy‐to‐follow approach for the calculation of pseudomorphic epitaxial strain in arbitrary heterostructures is presented. The procedure is suitable for the general case of triclinic materials and arbitrary epitaxial plane. Special cases for crystals of higher symmetry are derived from that. Besides trivial operations, only two inversions of 3 × 3 matrices are necessary.